trigonometry

Asked by chandant | 15th Apr, 2011, 06:46: AM

Expert Answer:

The question which you have posted is wrong. The correct statement of the question is as follows:
3sin2A+ 2sin2B =1     ... (1)
and 3 sin2A -2sin2B =0  ... (2)
 
Following is the solution:
 
From equation (1), we have:
3sin2A = 1 - 2sin2B = cos 2B    ... (3)
From (2), we have:
3 sin2A = 2 sin 2B                   ... (4)
 
Consider cos (A + 2B) = cosA cos 2B - sin A sin 2B
                               = cosA (3sin2A) - sin A (3 sin 2A/2)      [Using (3) and (4)]
                               = 3 cosA sin2A - sin A (3 sin A cosA)     [Since, sin 2A = 2 sinA cos A]
                               = 3 cosA sin2A - 3 sin2 A cosA
                               = 0
Thus, A + 2B = ?/ 2       
[Since, cos ?/ 2 = 0]

Answered by  | 5th May, 2011, 10:44: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.